Pengembangan Produk dan Pemasaran Desa Wisata Digital: Program Insentif Pengabdian Masyarakat Terintegrasi dengan Merdeka Belajar Kampus Merdeka Berbasis Kinerja Indikator Kinerja Utama bagi Perguruan Tinggi Swasta Tahun 2022 - Hermawan, Hary; Anwari, Hamdan; Nugroho, Dhimas Setyo; Hendrajaya, Agnestasya Monica Putri; Chandrawati, Nadita Eka; Girsang , Pitta Theresia br (Jurnal Abdimas Pariwisata, 2023)
The development of digital tourism village products and marketing. In the competitive tourism business, digital marketing has become a crucial need in this non-restricted space and time era. The Sekolah Tinggi Pariwisata AMPTA is trying to solve various problems in the Garongan Tourist Village through Community Service (PKM), which includes: (1) Facilitating the creation of company profile videos and vlogs for the Garongan tourist village; (2) Training in the creation of digital promotion content on Instagram and Facebook; (3) Training in the creation of vlog content for TikTok promotion; (4) Training in optimizing YouTube for digital promotion content; (5) Training in optimizing landing pages and using paid advertising; (6) Facilitating and mentoring in the creation of websites and landing pages for the Garongan Tourist Village; (7) Facilitating and mentoring in the creation of Instagram content. This activity is carried out with the support of integrated community service incentives from the Merdeka Belajar Kampus Merdeka (MBKM) scheme of the Community Empowerment Program in 2022 by the Director General of Higher Education Research and Technology, Ministry of Education, Culture, Research, and Technology.